Competency Analysis And Job Placement of PTPN 1 Regional 7 UNIT Senabing Lahat Employees - Maya Yulia Safitri; Delvina Yulanda; Nidyawati Nidyawati (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine how competency and job placement partially and simultaneously influence employee performance at PTPN 1 Regional 7 Unit Senabing Lahat. The sample size for this study was 69 respondents. The sampling method used was incidental sampling. This quantitative study employed multiple linear regression analysis, processed using SPSS, resulting in a regression equation Y = 4,535 + 0,629X1 + 0,267X2. The results showed a significant effect between competency and employee performance at PTPN 1 Regional 7 Unit Senabing Lahat, and a significant effect between job placement and employee performance at PTPN 1 Regional 7 Unit Senabing Lahat. The F-test indicated that competency and job placement simultaneously influenced employee performance at PTPN 1 Regional 7 Unit Senabing Lahat.